Framing Polish-Jewish Relations Through Shakespeare in Post-war and Contemporary Polish Theatre - Kowalski, Tomasz (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The paper aims to analyse how the staging of Shakespeare’s texts in post-war and contemporary Poland reflected the indifferent and hostile attitudes of Poles towards Jews, particularly during the Holocaust, and the distortions and gaps in the collective memory regarding the events. In the first part, the author focuses on Hamlet Study (dir. Jerzy Grotowski) performed in 1964 by Laboratory Theatre of 13 Rows in Opole, which is symptomatic of silencing the matter during the communist period. The second part draws from the statement of Jan Ciechowicz, a Polish theatre historian, who claimed that “the Holocaust killed Shylock for Polish stage.” While verifying it, the author analyses selected aspects of three productions directed by Krzysztof Warlikowski (The Tempest (2003), The Merchant of Venice (1994) and The African Tales by Shakespeare (2011)) and juxtaposes them against the background of the changes in collective memory. He argues that the most cogent productions concerning Polish attitudes towards Jews are those that position the audience as witnesses of the acts of re-enacted violence and thus provoke an affective response.